Peran Pembiayaan Produktif BMT Pahlawan Dalam Peningkatan Kesejahteraan Anggota - Ullya Nindyaningtyas; Meri Indri Hapsari (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research is to assess the role played by Baitul Maal Wattamwil (BMT) in increasing welfare of its member. This research adopts a quantitative approach through empirical analysis using Pahlawan Baitul Maal Wattamwil (BMT) located in Tulungagung as the subject of research.Several tools of analysis used in this research are: The Headcount Ratio, The Poverty Discrepancy Ratio, The Income Discrepancy Ratio, The Fooster, Greer and Thorbeck (FGT) index and the Threshold of Trade.